CORPORATE TAX AVOIDANCE STRATEGIES: ANALYZING THE ROLE OF ACCOUNTING STANDARDS AND REGULATIONS - Doloan, Arisanjaya (Penelitian dan Pengembangan Ilmu, 2025)
Corporate tax avoidance has emerged as a critical issue in the global economy, especially among multinational companies (MNCs) that seek to minimize their tax liabilities through various legal strategies. This research analyzes the growing trend in corporate tax avoidance in response to changes in accounting standards and tax regulations, with a particular focus on the implications of the OECD's Base Erosion and Profit Shifting (BEPS) initiative and the introduction of a global minimum tax. Using a systematic literature review approach, this research synthesizes findings from recent studies to identify key themes such as regulatory adaptation, the impact of digitalization on transfer pricing, the strategic use of tax havens, and changes in financial reporting practices. The research results show that MNCs are increasingly adopting their tax strategies to navigate a complex regulatory environment while leveraging digital business models and domestic tax incentives. This paper provides valuable insights for policymakers, regulators and practitioners aiming to improve tax compliance and transparency in an era of rapid economic transformation.